Pengembangan Pariwisata Berbasis Budaya Berdasarkan Ketentuan Undang-Undang Nomor 10 Tahun 2009 Di Kabupaten Sleman - T. Diana Ethika (Kajian Hukum, 2016)
The research under the title "The Development of Cultural Tourism Under the Provisions of Regulation No. 10 Year 2009 In Sleman " will discuss the efforts of the local government of Sleman in tourism development based on culture and the extent of community involvement in the development of culture-based tourism in Sleman. The research method used in discussing the results of this research is qualitative descriptive method.There are various efforts made by the local government of Sleman in developing culture-based tourism, those efforts include the increasing of promotional activities through various ways such as through local-printed media / newspapers, through electronic media, the distribution of brochures / leaflet, banners in strategic places. As much as possible try to facilitate a group of people who want cultural activities that they have been reappointed as a local cultural activities that can be used as a tourist attraction. Immediately draft of the Master Plan for Tourism Development (Rencana Induk Pengembangan Kepariwisataan (RIPP)) can be endorsed so that the local government of Sleman District will have a clear direction on development plans for tourism in the area until 2025, which will come. Soon, the draft Regulation (draft) (Rancangan Peraturan Daerah (RAPERDA)) regarding the conduct of tourism, fiscal year 2017, planned to be proposed in the incensement of the promotion budget as an effort to increase the number of tourist visits to Sleman.The community is involved in planning activities of Sleman tourism calendar. The community is involved also in the promotion of tourism and sustainable development conducted against groups in society that has the cultural potential of which is used as a tourist attraction.